Precipitation of the Mediterranean origin in Poland – its seasonal and long-term variability - Degirmendžić, Jan; Kożuchowski, Krzysztof (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2015)
The article presents the results of the analysis of precipitation in Poland associated with cyclones moving from the Mediterranean Sea to East-Central Europe (Mediterranean Cyclonal Precipitation – MCP). The MCP accounts for about 10% of the total amount of precipitation in Poland. Average daily sum of MCP constitutes approximately 150% of daily amount of all precipitation in Poland. The MCP amount reaches its maxima at the end of April and in the mid-August. The highest MCP occurs in the Carpathians and the Sudetes as well as over stripes of land extending northward and covering the central-western and eastern parts of the country. In the years 1958–2008, the mean annual MCP was characterized by a significant decreasing trend - the MCP sum reduced by 29 mm, i.e. ca. 42% of its multiannual value.
Keywords: Mediterranean precipitation; seasonality; long-term changes; Poland